Pengabdian Masyarakat Bagi Wisata Bojong Asri Tangguh dan Berdaya Saing - Setyawan, Agustinus Hary; Nugraeni, Nugraeni; Wafa, Zaenal (Pencerah, 2023)
This community service program aims to develop Wisata Bojong Asri as an education and marine environment-based destination. Bojong Asri, located near Pantai Depok in Bantul, Yogyakarta, has several problems from financial monitoring, tourist service dan the place branding. The problems need the solutions through several programs. The engagement programs involves three key aspects: marketing through social media, bookkeeping, and English tour guides training. This community service was conducted through three stages as the method of this community service: training, mentoring, and evaluation. The social media branding and marketing training helped the Bojong Asri team to create and manage various platforms effectively. Additionally, the bookkeeping training improved their financial management skills. Finally, tour guide training focuses on basic english speaking skills for tour guides and how to guide foreign tourists well. This engagement not only impacted to Bojong Asri's development but also enhanced the overall image, income and revenue generation of the tourism destination.